XX-CENTURY UZBEKISTAN BOOK GRAPHICS ART DISCUSSION CLASS USING MODERN PEDAGOGICAL METHODS (Web of Teachers: Inderscience Research, 2025)
In this conversation lesson, the book graphics art of 20th century Uzbekistan will be analyzed and the possibilities of using modern pedagogical methods to convey this topic to students will be discussed. An interactive approach, clustering, 'thought wheels', 'brainstorming', group work, and the use of visual materials are planned to stimulate students' interest in the subject during the lesson. Examples of book graphics created in the 20th century, famous artists – the artists who decorated Abdulla Qodiriy's works and their styles will be discussed. The conversation will be conducted based on methods aimed at developing students' independent thinking, analysis, and art evaluation skills. The use of ICT tools, presentations, illustrations, and videos will enhance visual retention in the lesson. Thus, modern pedagogical approaches in studying the history of art and culture will deepen students' knowledge and foster creative thinking.